Alkaline-Stable, In Situ Menshutkin Coat and Curable Ammonium Network: Ion-Solvating Membranes for Anion Exchange Membrane Water Electrolyzers - Jung, Jiyoon; Park, Young Sang; Choi, Gwan Hyun; Park, Hyun Jin; Ahn, Cheol-Hee; Hwang, Seung Sang; Lee, Albert S. (John Wiley & Sons Inc., 2023)
Anion exchange membranes fabricated through a one-step Menshutkin reaction with down-selected multifunctional alkyl halides and multifunctional tertiary amines within an ion-solvating matrix, poly(ethylene-co-vinyl alcohol), yielded alkaline-stable ammonium network polymers. Due to the vast simplicity in fabrication due to the quaternization/Menshutkin reaction between tertiary amine and alkyl bromides, which does not evolve any by-products that require purification, alkaline-stable membranes were fabricated in one step through facile mixing and curing of alkaline-stable ammonium network forming monomers. Prepared membranes showed controllable ion exchange capacity (IEC), conductivity, and mechanical strength by controlling of poly(ethylene-co-vinyl alcohol) amount which is an ion-solvating polymer. The selection of ammonium network chemical structure allowed for flawless retention of IEC and conductivity under conditions of 70 degrees C, 1M KOH of over 300 h. Anion exchange membrane electrolysis membrane electrode assembly tests with optimized membranes showed a greater performance (1.78 A/cm2 at 2.0 V) and more enhanced water electrolyzer durability than that of commercial anion exchange membrane.